2021
DOI: 10.1002/syst.202100010
|View full text |Cite
|
Sign up to set email alerts
|

How Glycine Betaine Modifies Lipid Membrane Interactions

Abstract: Ubiquitous in the cellular milieu, small organic compounds termed osmolytes help to regulate the response to environmental stress. Elasmobranchii, such as sharks, accumulate high concentrations of several osmolytes, most notably urea, trimethylamine N‐oxide (TMAO), and glycine betaine (GB). These three compounds are used to osmoregulate the organism's body fluids, so that they counteract seawater salinity, as well as the destabilizing effects of hydrostatic pressure on cells and their molecular components. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…watsonii C-113 own glycine betaine (GBT) transport gene opuD . GBT has been found common in bacteria as osmotic molecules ( Shakhman and Harries, 2021 ). A variety of soil and aquatic bacteria have catabolic pathways that convert choline to glycine in multiple steps via GBT ( Figure 1E ), using both choline and GBT as the sole carbon and nitrogen sources ( Wargo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…watsonii C-113 own glycine betaine (GBT) transport gene opuD . GBT has been found common in bacteria as osmotic molecules ( Shakhman and Harries, 2021 ). A variety of soil and aquatic bacteria have catabolic pathways that convert choline to glycine in multiple steps via GBT ( Figure 1E ), using both choline and GBT as the sole carbon and nitrogen sources ( Wargo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of TMAO led to further increase in thickness, at least up to pressures of ~ 800 bar when the membrane as a whole entered a gel phase. A recent study of the effects of glycine betaine on model membranes showed that GB has effects similar to those of TMAO, albeit the strengths of the effects were generally lower (Shakhman and Harries 2021 ).…”
Section: Temperaturementioning
confidence: 99%
“…Therefore, the co-occurrence of urea and TMAO in elasmobranchs may help to thwart loss of optimal liquid–crystalline states in deep-living members of this group of fishes. In fact, in vitro studies using model membranes show that this type of counteracting solute effect does apply to membranes as well as to proteins (Shakhman and Harries 2021 ).…”
Section: Temperaturementioning
confidence: 99%